Analisis Politik Dalam Bisnis Pada Era Globalisasi - Wanda Nilam Sari Br. Harefa; Sasmi Ebigael Sinaga; Bonaraja Purba (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The purpose of this study is as a foundation to find out how business politics occur in today's digitalization era. The discussion focused on seeing how business can develop in the era of globalization and digitalization while maintaining the basis / rules of doing business. So based on the results and discussion of this study, it can be concluded that politics in doing business in the era of globalization still occurs.